A ‘star performer’ megaproject? Linkages and the Mozal aluminium smelters in Mozambique (1998-2017) - Wilhelm, Cindy (Student Undergraduate Research E-journal!, 2018)
Despite the increasing appetite for precious commodities, resource- rich developing countries are confronted with numerous challenges regarding their resource-based development. This thesis analyses the case of Mozambique where the Mozal aluminium smelter ‘megaproject’ was seen as an opportunity for resource-based development. By following Hirschman’s linkages theory on resource-based development through diversification of the economy by an upscale on the value chain, this thesis comes to the conclusion that in terms of tax income, the use of local contractors and suppliers and the diversification of the aluminium industry, numerous challenges remain